2008
DOI: 10.1016/j.cell.2007.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in the Pathogenesis of Disease

Abstract: Autophagy is a lysosomal degradation pathway that is essential for survival, differentiation, development, and homeostasis. Autophagy principally serves an adaptive role to protect organisms against diverse pathologies, including infections, cancer, neurodegeneration, aging, and heart disease. However, in certain experimental disease settings, the self-cannibalistic or, paradoxically, even the prosurvival functions of autophagy may be deleterious. This Review summarizes recent advances in understanding the phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

55
5,651
3
49

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 6,308 publications
(5,758 citation statements)
references
References 100 publications
55
5,651
3
49
Order By: Relevance
“…30 In the context of cancer, autophagy induction may have oncopreventive and improve therapeutic outcome after chemotherapy effects. 18,19,3133 In addition, starvation, which is one of the best-known inducers of autophagy, increases the resistance of mice against the toxic effects of anthracycline-based chemotherapy at the same time that it improves tumor growth reduction.…”
Section: Resultsmentioning
confidence: 99%
“…30 In the context of cancer, autophagy induction may have oncopreventive and improve therapeutic outcome after chemotherapy effects. 18,19,3133 In addition, starvation, which is one of the best-known inducers of autophagy, increases the resistance of mice against the toxic effects of anthracycline-based chemotherapy at the same time that it improves tumor growth reduction.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have demonstrated that the antisenescence effects of AMPK are closely involved in the induction of autophagy (Levine & Kroemer, 2008; Salminen & Kaarniranta, 2012), and the physiological aging process is associated with a decline in the efficiency of autophagic degradation, which occurs in autolysosomes and largely limits autophagic flux (Mijaljica et al ., 2010). Despite the fact that the number of autophagosomes increased in senescent cells, our result strongly supports the notion that autolysosomal degradation and autophagic flux were attenuated in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunctional autophagy has been observed in aging and age‐related diseases (Levine & Kroemer, 2008; Lipinski et al ., 2010). Autophagy is a homeostatic cellular recycling mechanism responsible for degrading injured or dysfunctional cellular organelles and proteins in all living cells (Mizushima et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these data increase our understanding of the molecular pathways regulating autophagy and can be used as a resource to identify (novel) factors involved in autophagy regulation. Because autophagy has been implicated in numerous diseases, a better understanding of the molecular pathways and transcription factors regulating autophagy might lead to the development of novel strategies aimed at restoring autophagy levels in the context of disease, for example therapies targeting EGR1 expression [51]. …”
Section: Discussionmentioning
confidence: 99%